Bringing Hirschman Back In: Conceptualizing Transnational Migration as a Reconfiguration of "Exit", "Voice", and "Loyalty" - Bert Hoffmann (German Institute of Global and Area Studies (GIGA), 2008)
Albert O. Hirschman's scheme of 'exit and voice', long a classic in the study of migration and its political implications, was conceived within the framework of 'methodological nationalism'. However, the rise of migrant transnationalism is eroding the classic migration paradigm. Combining theoretical considerations with empirical insights from Latin American cases, this paper argues that a critical reappraisal of Hirschman's scheme provides a helpful heuristic tool for conceptualizing the new character of today's transnational migration. Whereas in the traditional approach to international migration the options of exit, voice, and loyalty are considered to be mutually exclusive, transnational migration can be defined precisely by the overlapping and simultaneity of these categories. – – Albert O. Hirschmans Modell von 'Abwanderung und Widerspruch' ('exit and voice'), das lange ein klassischer Ansatz für Studien zu den politischen Implikationen von Migration war, wurde im Rahmen des 'methodologischen Nationalismus' entwickelt. Der zunehmend transnationale Charakter gegenwärtiger Migration unterhöhlt jedoch das klassische Migrationsparadigma. Der vorliegende Beitrag verbindet theoretische Überlegungen mit empirischen Erkenntnissen neuerer Migration aus Lateinamerika; auf dieser Grundlage argumentiert er, dass eine kritische Revision des Hirschman'schen Modells ein wertvolles heuristisches Werkzeug darstellt, um den neuen Charakter der transnationalen Migration konzeptionell zu fassen. Während im traditionellen Verständnis zwischenstaatlicher Migration die Optionen von Abwanderung, Widerspruch und Loyalität als sich wechselseitig ausschließend erscheinen, definiert sich transnationale Migration just durch die Überlappung und die Gleichzeitigkeit dieser Kategorien.
Keywords: 300; migration; transnationalism; 'exit and voice'; Latin America; 'methodological nationalism'